2018
DOI: 10.3389/fpsyt.2018.00276
|View full text |Cite
|
Sign up to set email alerts
|

Association of Depression and Anxiety With the 10-Year Risk of Cardiovascular Mortality in a Primary Care Population of Latvia Using the SCORE System

Abstract: Background: Depression and anxiety have been recognized as independent risk factors for both the development and prognosis of cardiovascular (CV) diseases (CVD). The Systematic Coronary Risk Evaluation (SCORE) function measures the 10-year risk of a fatal CVD and is a crucial tool for guiding CV patient management. This study is the first in Latvia to investigate the association of depression and anxiety with the 10-year CV mortality risk in a primary care population.Methods: This cross-sectional study was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 35 publications
1
21
0
2
Order By: Relevance
“…In addition, studies that related anxiety and depression disorders (ADD) and CVD in primary care centers suggest that depressive disorders could be associated with a very high risk of mortality from cardiovascular causes. 13 Despite the prevalence and importance of these conditions in primary care, the rates of identification and treatment remain very low, with less than half of the depressive episodes identified correctly. 14 The prevalence of depression in this population ranged from 21.4% to 31.0%, according to a Brazilian multicenter study conducted in four large cities.…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…In addition, studies that related anxiety and depression disorders (ADD) and CVD in primary care centers suggest that depressive disorders could be associated with a very high risk of mortality from cardiovascular causes. 13 Despite the prevalence and importance of these conditions in primary care, the rates of identification and treatment remain very low, with less than half of the depressive episodes identified correctly. 14 The prevalence of depression in this population ranged from 21.4% to 31.0%, according to a Brazilian multicenter study conducted in four large cities.…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…This information was used to develop diagnostic and treatment algorithms for depression in primary care in Latvia (Vrublevska et al, 2017;Rancans et al, 2018). Other studies suggested that patients with a Systematic COronary Risk Evaluation (SCORE) 10% could benefit from screening and early treatment of depression to potentially delay its development and improve the prognosis of cardiovascular disease (Ivanovs et al, 2018). However, while the doctors in our study were ready to introduce routine screening of depression in their practices, the US Preventive Services Task Force recommended against routine screening unless "staff-assisted depression care supports are in place to assure accurate diagnosis, effective treatment and follow-up".…”
Section: Discussionmentioning
confidence: 99%
“…Changes in older people's life, with a decreasing socialfamiliar support, loss of occupational status and decrease of social inclusion, are often a reason to trigger feelings of solitude and loneliness, leading to depressive states (Petitte et al, 2015). A state of good mental health is associated with better social networks (Ivanovs et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…week (Ivanovs et al, 2018). 10 of the 30 items are scored with 1 point when the answer is "No" (items 1, 5, 7, 9, 15, 19, 21, 27, 29 and 30) and the other 20 are scored with 1 point when the answer is "Yes".…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation